Seasonal increases in fish trophic niche plasticity within a flood‐pulse river ecosystem (Tonle Sap Lake, Cambodia). Issue 7 (12th July 2017) - Pool, Thomas; Holtgrieve, Gordon; Elliott, Vittoria; McCann, Kevin; McMeans, Bailey; Rooney, Neil; Smits, Adrianne; Phanara, Thach; Cooperman, Michael; Clark, Sydney; Phen, Chheng; Chhuoy, Samol
Abstract: Species' responses to seasonal environmental variation can influence trophic interactions and food web structure within an ecosystem. However, our ability to predict how species' interactions will vary spatially and temporally in response to seasonal variation unfortunately remains inadequate within most ecosystems. Fish assemblages in the Tonle Sap Lake (TSL) of Cambodia—a dynamic flood‐pulse ecosystem—were studied for five years (2010–2014) using stable isotope and Bayesian statistical approaches to explore both within‐ and among‐species isotopic niche variation associated with seasonal flooding. Roughly 600 individual fish specimens were collected during 19 sampling events within the lake. We found that fishes within the same species tended to have a broader isotopic niche during the wet season, likely reflecting assimilation of resources from either a wider range of isotopically distinct prey items or a variety of habitats, or both. Furthermore, among‐species isotopic niches tended to overlap and range more broadly during the wet season, suggesting that floodplain inundation promotes exploitation of more diverse and similar resources by different species in the fish community. Our study highlights that the flood‐pulse dynamic that is typical of tropical aquatic ecosystems may be an essential element supporting freshwater fish community structure and the fish diversity that underpins the TSL food web. This flow regime is currently threatened by regional dam development, which may in turn impact the natural function and structure of the fishery food web.